Effect of liming on nickel bioavailability and toxicity to oat and soybean grown in field soils containing aged emissions from a nickel refinery. (7th November 2016) - Cioccio, Stephen; Gopalapillai, Yamini; Dan, Tereza; Hale, Beverley
Abstract: Remediation of soils elevated in trace metals so that the soils may provide ecosystems services is typically achieved through pH adjustment or addition of sorbents. The present study aimed to generate higher‐tier in situ toxicity data for elevated nickel (Ni) in soils with and without lime addition and to explore the effect of liming on soil chemistry and bioavailability of Ni to plants. A multiyear study of agronomic yield of field‐grown oat and soybean occurred in 3 adjacent fields that had received air emissions from a Ni refinery for 66 yr. The soil Ni concentration in the plots ranged between 1300 mg/kg and 4900 mg/kg, and each field was amended with either 50 Mg/ha, 10 Mg/ha, or 0 Mg/ha (or tonnes/ha) of crushed dolomitic limestone. As expected, liming raised the pH of the soils and subsequently reduced the plant availability of Ni. Toxicity thresholds (effective concentrations causing 50% reduction in growth) for limed soils supported the hypothesis that liming reduces toxicity. Relationships were found between relative yield and soil cation exchange capacity and between relative yield and soil pH, corroborating findings of the European Union Risk Assessments and the Metals in Asia studies, respectively. Higher tier ecotoxicity data such as these are a valuable contribution to risk assessment for Ni in soils. Environ Toxicol Chem 2017;36:1110–1119. © 2016 SETAC